1997
DOI: 10.1161/01.atv.17.11.2341
|View full text |Cite
|
Sign up to set email alerts
|

CLA-1 Is an 85-kD Plasma Membrane Glycoprotein That Acts as a High-Affinity Receptor for Both Native (HDL, LDL, and VLDL) and Modified (OxLDL and AcLDL) Lipoproteins

Abstract: Lipoprotein metabolism is regulated by the functional interplay between lipoprotein components and the receptors and enzymes with which they interact. Recent evidence indicates that the structurally related glycoproteins CD36 and SR-BI act as cell surface receptors for some lipoproteins. Thus, CD36 has been reported to bind oxidized LDL (OxLDL) and acetylated LDL (AcLDL), while SR-BI also binds native LDL and HDL. The cDNA of human CLA-1 predicts a protein 509 amino acids long that displays a 30% and an 80% am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
165
0
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(175 citation statements)
references
References 47 publications
6
165
0
4
Order By: Relevance
“…In this regard it is noteworthy that high affinity binding of HDL to a surface receptor called CD36, which in many ways resembles SR-BI (41), is not sufficient to ensure efficient cellular selective lipid uptake or unesterified cholesterol efflux. Thus, CD36, which shares many structural and functional similarities to SR-BI (41), was initially shown to bind HDL tightly (22,25) but not mediate efficient selective lipid uptake (25). These findings were independently confirmed (62) and extended by the analysis of cholesterol efflux (48).…”
Section: Effects Of Apoa-i Mutations On Binding and Cholesterol Efflumentioning
confidence: 96%
See 1 more Smart Citation
“…In this regard it is noteworthy that high affinity binding of HDL to a surface receptor called CD36, which in many ways resembles SR-BI (41), is not sufficient to ensure efficient cellular selective lipid uptake or unesterified cholesterol efflux. Thus, CD36, which shares many structural and functional similarities to SR-BI (41), was initially shown to bind HDL tightly (22,25) but not mediate efficient selective lipid uptake (25). These findings were independently confirmed (62) and extended by the analysis of cholesterol efflux (48).…”
Section: Effects Of Apoa-i Mutations On Binding and Cholesterol Efflumentioning
confidence: 96%
“…SR-BI binds HDL and rHDL, at least in part via apoA-I (14,15). In addition, it can bind other lipoproteins (21,22) and exhibits complex binding properties consistent with multiple classes of binding sites or modes of binding different ligands (19,23,24). On binding lipoproteins, SR-BI mediates both selective cholesteryl ester uptake from the lipoprotein to the cells (19,(23)(24)(25) and bi-directional unesterified cholesterol movement (23,26,27).…”
mentioning
confidence: 99%
“…Further studies of the human homologue demonstrated that it also is a multilipoprotein receptor that binds HDL, LDL, and VLDL. 2,10 Further analysis in vivo in mice and rats has supported a role for SR-BI in cholesterol metabolism. Targeted disruption of apoAI, the major protein component of HDL, leads to an increase in SR-BI expression in the adrenal glands of mice, 11 where HDL-C is used for steroid hormone synthesis.…”
mentioning
confidence: 99%
“…Many lipoprotein receptors have been characterized in eukaryotes, to date only cubilin (22) and members of the CD36 superfamily of scavenger receptors (23)(24)(25) bind native HDL (without requiring ApoE as a component). The CD36 superfamily of scavenger receptors bind and take up both native HDL and LDL as well as other polyanionic ligands, including oxidized and acetylated LDL (26).…”
mentioning
confidence: 99%